A problemática do remanso dos eixos de macrodrenagem nas galerias urbanas: estudo de caso sobre a modelagem da cheia do Rio Poty no ano de 2009 em Teresina-PI - Silva, Maria José Carvalho (2014)
The city of Teresina, Piauí state capital, is intersected by rivers Parnaíba and Poty, the last tributary to the first, within the urban area of ​​Teresina. The Parnaíba River controls a watershed of 237,000 square kilometers upstream of Teresina, while the river Poty, controls a watershed of 51,400 km². The main hydrological characteristic of floods in the Parnaíba and Poty rivers is that Parnaíba River floods are likely to partial control from the gates of Hydroelectric Power Plant (HPP) Good Hope, whereas such control does not exist to floods arising from the Poty River basin. This study examined the question interference flooding of Poty river with minor drainage system formed by affluent urban galleries cross the same, noting the possibility of drowning and backwater Poty river on the galleries certain conditions of hydrological floods. Analyzed the case of the full 2009 in the transverse drainage system to Poty River, which caused the flood diverse neighborhoods, because of backwater due to the increase of share of the Poty river water level d greater than the level of the upper generating lines of the galleries cross. It was found that, because of desague quotas of galleries Spring neighborhood in Poty river, the floods of the river with two-year return period (TR = 2 years), are sufficient to promote the reverse flow in the gallery system and the Flood connected urban areas. It is concluded that there is need for structural measures to solve this problem, from, or control of Poty river floods through the sump, as a future dam Castle of Piauí, or from use of urban detention basins, locks tide and pumping system of rainwater in interconnected basins with the Poty River.